Transforming Pharmaceutical Supply Chain Management with Innovative SAP Technologies - Hariprasad Mandava (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The pharmaceutical industry faces significant challenges related to supply chain management, including stringent regulatory requirements, the need for precise inventory management, and the constant pressure to reduce costs. Innovative SAP (Systems, Applications, and Products) technologies have emerged as powerful tools to optimize the pharmaceutical supply chain, offering solutions for enhanced visibility, data-driven decision-making, and compliance management. This manuscript explores the role of innovative SAP technologies in pharmaceutical supply chain management, focusing on key solutions such as SAP Integrated Business Planning (IBP), SAP S/4HANA, SAP Advanced Track and Trace, and SAP Digital Supply Chain. The paper also highlights how these technologies can address industry challenges, improve operational efficiency, and ensure end-to-end traceability and security.